Exploring healthcare professionals’ motivation to attend two postgraduate education programs at the University of Bern in Switzerland: A qualitative interview study - De la Rosa, Melanie; Schmitz, Felix M.; Berger-Estilita, Joana; Tekian, Ara; Guttormsen, Sissel (GMS Journal for Medical Education)
Introduction: Postgraduate education programs for healthcare professionals have seen rising demand due to socio-demographic shifts, digitalisation, and evolving healthcare models. This trend underscores the need for providers to offer high-quality, innovative teaching and learning opportunities that align with participants’ needs and interests. Understanding the motivations behind enrolment is essential for tailoring curricula and didactical methods effectively. This study explores key motivational factors influencing healthcare professionals’ decisions to join postgraduate education programs. The findings aim to inform curriculum planning to ensure that programs better meet the specific needs and interests of their learners. Methods: We conducted a qualitative study with N=23 semi-structured interviews with 13 students from the Master’s program in Medical Education (MAS) and 10 with students from the Certificate of Advanced Studies in Palliative Care (CAS). The interviews were thematically analysed to identify common and differentiating motivational factors, with coding conducted independently by two researchers to enhance reliability. Results: This study identified both general and program-specific motivational factors among MAS and CAS participants. MAS participants frequently mentioned career development, professional advancement, and empowerment as key motivations. CAS participants, on the other hand, placed greater emphasis on content-specific motivations. For both groups, local proximity and the education format played a crucial role in their decision to enrol in these programs. In addition, seven implications for program planning were identified to enhance the alignment of postgraduate education with participants’ needs. Discussion: With the method of qualitative analysis and the focus on post-graduate program-participants’ needs and interests, new insights on motivation to attend postgraduate education were gained. The significance of these findings is supported by existing literature. Consequently, these results offer valuable implications for the planning and development of postgraduate education programs.